1988
DOI: 10.1037/0735-7044.102.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Memory enhancement with posttraining intraventricular glucose injections in rats.

Abstract: Recent findings suggest that peripheral epinephrine enhancement of memory storage may be mediated in part by an increase in circulating glucose levels subsequent to epinephrine release or injection. Because glucose, unlike epinephrine, has ready access to the central nervous system, it is possible that glucose acts directly on central processes to enhance memory. To test this possibility, rats were trained on a one-trial inhibitory avoidance task and received immediate or delayed injections of glucose in artif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 37 publications
0
36
1
Order By: Relevance
“…This is the first study demonstrating the memorymodulating effects of glucose on preweanling rats in an infantile amnesia paradigm. In this case, glucose presumably either directly (Gold, 1995;Lee, Graham, & Gold, 1988) or through some peripheral mechanism (Messier & White, 1987;White, 1991;Williams & Jensen, 1991) affected the activity of the neurological substrates in the brain to allow for enhanced retention of the prior learning episode.…”
Section: Discussionmentioning
confidence: 97%
“…This is the first study demonstrating the memorymodulating effects of glucose on preweanling rats in an infantile amnesia paradigm. In this case, glucose presumably either directly (Gold, 1995;Lee, Graham, & Gold, 1988) or through some peripheral mechanism (Messier & White, 1987;White, 1991;Williams & Jensen, 1991) affected the activity of the neurological substrates in the brain to allow for enhanced retention of the prior learning episode.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, it has been shown that the insulin-sensitive glucose transporter GLUT4 is present in several brain regions such as the hippocampus [182]. On the other hand, the administration of glucose both peripherally [183][184][185] and centrally [186] has been shown to enhance memory. In contrast to this view, Zhao et al [187] believe that improvement of memory by insulin cannot be due to a direct glucoregulatory effect because the brain mainly expresses the two insulin-insensitive glucose transporters, including GLUT1 and GLUT3.…”
Section: How Insulin Affects Memorymentioning
confidence: 99%
“…Findings from a number of studies indicate that an epinephrine-induced increase in circulating glucose concentrations may mediate epinephrine's effects on memory [7] and considerable evidence supports the hypothesis that glucose modulates memory by direct brain action [8][9]. On the other hand, peripherally administered L-glucose, an isomer of glucose, that does not readily enter the brain, also facilitates retention performance [10].…”
Section: Introductionmentioning
confidence: 99%